Colorectal cancer in younger adults from a Bi‐National Colorectal Cancer Audit registry. Issue 3 (28th August 2020) - Kong, Joseph C.; Su, Wai Kin; Ng, Chu Woon; Guerra, Glen R.; Chakraborty, Joy; Lutton, Nicholas; Morris, Bradley; Gourlas, Peter
Abstract: Background: The incidence of colorectal cancer (CRC) in younger adults (<50 years old) is rising worldwide, at a rate of 1% per annum since mid‐1980s. The clinical concern is that younger adults may have more advanced disease leading to poorer prognosis compared to their older cohort due to lack of screening. Therefore, the aim of this study is to assess the incidence and short‐term outcomes of colorectal cancer in younger adults. Methods: This is a retrospective study from a prospectively maintained bi‐national database from 2007 to 2018. Results: There were 1540 younger adults diagnosed with CRC, with a rise from 5.8% in 2007 to 8.4% in 2018. Majority had lower American Society of Anaesthesiologists (ASA) scores (89%), rectal cancers (46.1%) and higher tumour stage (65.4%). As a consequence, they were likely to have higher circumferential resection margin positivity (6%, P = 0.02) and to receive adjuvant chemotherapy (57.1%, P < 0.001) compared to their older cohort. Multivariate analysis showed disadvantaged socioeconomic status (odds ratio (OR) 3.3, 95% confidence interval (CI) 1.37–7.94, P < 0.001) and increasing tumour stage (OR 14.9, 95% CI 1.89–116.9, P < 0.001) were independent predictors for circumferential resection margin positivity whereas being female (OR 0.71, 95% CI 0.53–0.95, P = 0.02), higher ASA score (OR 175.3, 95% CI 26.7–1035.5, P < 0.001), urgent surgery (OR 2.75, 95% CI 1.84–4.11, P < 0.001) and anastomotic leak (OR 5.02, 95% CI 3.32–7.58, P < 0.001) were predictors of inpatient mortality. Conclusion: There is a steady rise in the incidence of colorectal cancer in younger adults. Both physicians and younger adults should be aware of the potential risk of colorectal cancer (CRC) and appropriate investigations performed so not to delay the diagnosis. Abstract : In this manuscript, we show that there is a rising incidence in colorectal cancer in younger patients, defined as those aged less than 50 years old. There is also the trend towards advanced disease at diagnosis and left sided tumours, leading to poorer prognosis. Our manuscript highlights the need to increase education and awareness in the younger population regarding the signs and symptoms of colorectal cancer.